Byzantine and Early Islamic Rayed Lamps from South-Eastern Turkey - Laflı, Ergün; Buora, Maurizio (Folia Orientalia, 2021)
In this short paper, nine formerly unpublished rayed lamps from south-eastern Turkey, eight from Mardin and one from Malatya are being presented, belonging to a well-known type, starting from the end of the sixth century A.D., which became particularly widespread in the eighth century A.D. The article adds to a group of ‘rayed’ lamps from the Near East next few examples found in less accessible museums in Turkey and it also includes a useful historical sketch of the region during the Byzantine and Early Islamic period. The publication of these new specimens is valuable as the material from this area of modern Turkey is rarely published. While waiting for research on the many further lamps that are likely to be found in numerous museums to be published, this contribution helps us understand the variety of lamps and their area of diffusion, which stretches from northern Mesopotamia down to Palestine, including south-eastern Turkey, Syria, Lebanon and Israel.